Modified Vector Control Algorithm for Increasing Partial-Load Efficiency of Fractional-Slot Concentrated-Winding Surface PM Machines - EL-Refaie, A.M.; Jahns, T.M.; Reddy, P.B.; McKeever, J.W. (IEEE transactions on industry applications, 2008)
This paper presents a modified vector control algorithm for a fractional-slot concentrated-winding surface permanent magnet (SPM) machine that has been developed to maximize the machine's partial-load efficiency over a wide range of operating conditions. By increasing the amplitude of the negative d -axis current, the resulting increase in the stator copper losses can be more than offset by the reduction in the iron core losses achieved by lowering the stator d -axis flux amplitude. The effectiveness of this technique has been demonstrated using both analytical models and finite element analysis for a 55-kW (peak) SPM machine design developed for a demanding set of traction drive performance requirements. For this example, the modified control strategy increases the partial-load efficiency at 20% of rated torque by > 6% at 2000 r/min compared to the maximum torque/ampere algorithm, making the machine much more attractive for its intended application.